2021
DOI: 10.3390/cancers13123073
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies and Immune Checkpoint Inhibitors in Primary CNS Lymphoma

Abstract: This review article outlines the current development of emerging treatment strategies for primary central nervous system lymphoma, a rare brain tumor with, thus far, limited therapeutic options. Small molecule targeted tyrosine kinase inhibitors, immunomodulatory agents, and immune checkpoint inhibitors will be discussed. The mechanisms of action, results of completed clinical studies, ongoing clinical trials, and future perspectives are summarized. Among the most promising clinical developments in the field o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The histone lysine methyltransferase, KMT2D , has a higher mutation frequency in PCNSL patients than in de novo DLBCLs [ 21 , 22 ]. ROBO1 is mainly expressed in vascular endothelial cells and is involved in angiogenesis through the Slit-Robo signaling pathway [ 23 ]. In myeloma study, ROBO1 also regulates the cancer microenvironment by inducing cancer cells to homing, disseminating, and surviving [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The histone lysine methyltransferase, KMT2D , has a higher mutation frequency in PCNSL patients than in de novo DLBCLs [ 21 , 22 ]. ROBO1 is mainly expressed in vascular endothelial cells and is involved in angiogenesis through the Slit-Robo signaling pathway [ 23 ]. In myeloma study, ROBO1 also regulates the cancer microenvironment by inducing cancer cells to homing, disseminating, and surviving [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The whole brain radiation therapy (WBRT) in combination with chemotherapeutic agents such as methotrexate is still a more common treatment modality. And some studies ( Wirsching et al, 2021 ) have suggested that isitinib may be a more promising therapeutic agent. As immunotherapy becomes more popular, more immune agents such as PD-1/PD-L1 monoclonal antibodies are being used in oncology treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of these gains varies markedly in independent studies, ranging from 21% (4/19) [ 27 ] to 67% (28/42) [ 22 ]. Furthermore, a variable expression of PDL-1/PD-1 protein has been reported, and it remains unknown whether molecular aberrations correlate with the protein level (reviewed by Wirsching et al [ 48 ]). This raises questions regarding the technological approaches and cut-offs used to diagnose these aberrations.…”
Section: Molecular Pathogenesis Of Pcnslmentioning
confidence: 99%